2013
DOI: 10.1159/000354984
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell-Deficient KitW-sh Mice Develop House Dust Mite-Induced Lung Inflammation despite Impaired Eosinophil Recruitment

Abstract: Background: Mast cells are implicated in allergic and innate immune responses in asthma, although their role in models using an allergen relevant for human disease is incompletely understood. House dust mite (HDM) allergy is common in asthma patients. Our aim was to investigate the role of mast cells in HDM-induced allergic lung inflammation. Methods: Wild-type (Wt) and mast cell-deficient Kitw-sh mice on a C57BL/6 background were repetitively exposed to HDM via the airways. Results: HDM challenge r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…Although the mechanisms of tryptase-induced transmigration of eosinophils are not completely understood, some experimental studies leave no doubt about the involvement of tryptase in such processes. Decreased eosinophil recruitment to tissues is observed in mast cell-deficient mice (de Boer et al 2014), as well as in experimental models where the PAR2 receptor was blocked (Hyun et al 2008;Matos et al 2013). Moreover, the positive correlation observed in this study between numbers of tryptase-IR mast cells and eosinophils could be also interpreted as evidence for the role of tryptase in eosinophil survival.…”
Section: Discussionsupporting
confidence: 69%
“…Although the mechanisms of tryptase-induced transmigration of eosinophils are not completely understood, some experimental studies leave no doubt about the involvement of tryptase in such processes. Decreased eosinophil recruitment to tissues is observed in mast cell-deficient mice (de Boer et al 2014), as well as in experimental models where the PAR2 receptor was blocked (Hyun et al 2008;Matos et al 2013). Moreover, the positive correlation observed in this study between numbers of tryptase-IR mast cells and eosinophils could be also interpreted as evidence for the role of tryptase in eosinophil survival.…”
Section: Discussionsupporting
confidence: 69%
“…The HDM model used here is characterized by allergic inflammation eventually leading to pulmonary pathological features such as perivascular inflammation, interstitial inflammation, peribronchitis and oedema [17][18][19]. Using a semiquantitative scoring system to quantify lung pathology as a result of HDM exposure, we found that MyD88KO mice developed significantly less lung inflammation compared to control mice ( Fig.…”
Section: General But Not Myeloid or Lung Epithelial Myd88 Deficiencmentioning
confidence: 87%
“…Tryptase activity was determined in BALF as described before . In short, 10 μL 6‐mmol/L chromogenic tryptase substrate S‐2288 (Chromogenix Instrumentation Laboratory, Milan, Italy) was added to 70 μL 57 mmol/L Tris‐HCl (pH 8.3) in a 96‐well microtiter plate.…”
Section: Methodsmentioning
confidence: 99%